2014
DOI: 10.1002/ece3.955
|View full text |Cite
|
Sign up to set email alerts
|

Length of intervals between epidemics: evaluating the influence of maternal transfer of immunity

Abstract: The length of intervals between epidemic outbreaks of infectious diseases is critical in epidemiology. In several species of marine mammals and birds, it is pivotal to also consider the life history of the species of concern, as the contact rate between individuals can have a seasonal flux, for example, due to aggregations during the breeding season. Recently, particular interest has been given to the role of the dynamics of immunity in determining the intervals between epidemics in wild animal populations. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Several empirical studies have demonstrated individual variation in susceptibility, immune response and sickness behaviours across populations from different geographical locations (Adelman, Bentley, Wingfield, Martin, & Hau, ; Adelman, Kirkpatrick, Grodio, & Hawley, ; Gibson, Jokela, & Lively, ). Waning immunity from maternal antibodies or prior exposure to an infectious agent may also contribute to temporal lags in the availability of susceptible individuals on different host patches depending on the local history of exposure (Fouchet et al., ; Garnier, Gandon, Harding, & Boulinier, ; Garnier et al., ; Plowright et al., ). Importantly, behavioural and physiological processes may be linked through host–parasite feedbacks (Ezenwa et al., ; Gudelj & White, ; VanderWaal & Ezenwa, ).…”
Section: Future Directions: Addressing Global Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several empirical studies have demonstrated individual variation in susceptibility, immune response and sickness behaviours across populations from different geographical locations (Adelman, Bentley, Wingfield, Martin, & Hau, ; Adelman, Kirkpatrick, Grodio, & Hawley, ; Gibson, Jokela, & Lively, ). Waning immunity from maternal antibodies or prior exposure to an infectious agent may also contribute to temporal lags in the availability of susceptible individuals on different host patches depending on the local history of exposure (Fouchet et al., ; Garnier, Gandon, Harding, & Boulinier, ; Garnier et al., ; Plowright et al., ). Importantly, behavioural and physiological processes may be linked through host–parasite feedbacks (Ezenwa et al., ; Gudelj & White, ; VanderWaal & Ezenwa, ).…”
Section: Future Directions: Addressing Global Challengesmentioning
confidence: 99%
“…Waning immunity from maternal antibodies or prior exposure to an infectious agent may also contribute to temporal lags in the availability of susceptible individuals on different host patches depending on the local history of exposure Garnier, Gandon, Harding, & Boulinier, 2014;Garnier et al, 2012;. Importantly, behavioural and physiological processes may be linked through host-parasite feedbacks VanderWaal & Ezenwa, 2016).…”
Section: Accounting For Host Heterogeneitymentioning
confidence: 99%
“…Consequently local population abundance, haul-out density, animal movement and the seasonal timing of any future outbreak could all affect contact rate. In addition, a recent study investigated the effect of maternal immunity on estimating the inter-epidemic interval for PDV in Europe [ 225 ]. Depending on the model assumptions, this could range from 6 to 12 years.…”
Section: Epidemiologymentioning
confidence: 99%
“…In a peak year following an increase year, the seroprevalence in overwintered voles in spring approaches 100% (see Supplementary Material ), and consequently most of the young born to these females should have maternal antibodies. This influx of maternally protected newborns may delay transmission beyond the abundance peak, hence reducing the infection prevalence (Garnier et al, 2014 ). The existence of MatAb immunity in juveniles has been described in multiple hantavirus studies in both US and Europe (for an overview see Kallio et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%